2016
DOI: 10.2147/ndt.s98711
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward metabolic adverse events among patients with schizophrenia in Japan

Abstract: BackgroundMetabolic syndrome is a growing concern among patients with schizophrenia because metabolic abnormalities are widely regarded as a major risk factor for cardiovascular disease and premature death. The current study assessed attitudes toward metabolic adverse events among patients with schizophrenia.MethodsA brief questionnaire was constructed to investigate patient recognition of the following broad areas: dietary habits, lifestyle, self-monitoring, knowledge, and medical practice. Between January 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 46 publications
0
8
2
Order By: Relevance
“…Low intakes, or lower intakes than comparison groups, were found for fish 54 , 63 and nuts and vegetable oils 20 . Large intakes, or higher intakes than comparison groups, were found for carbonated beverages, 20 sweetened beverages, 30 soft drinks, 69 cakes and other sweets, 69 white bread, 43 hydrogenated oils 20 and fast food/takeaway foods 43 , 62 . In addition, one study found poor diet literacy 41 and one study found difficulties obtaining and/or cooking food 48 for people with SMI.…”
Section: Resultsmentioning
confidence: 91%
“…Low intakes, or lower intakes than comparison groups, were found for fish 54 , 63 and nuts and vegetable oils 20 . Large intakes, or higher intakes than comparison groups, were found for carbonated beverages, 20 sweetened beverages, 30 soft drinks, 69 cakes and other sweets, 69 white bread, 43 hydrogenated oils 20 and fast food/takeaway foods 43 , 62 . In addition, one study found poor diet literacy 41 and one study found difficulties obtaining and/or cooking food 48 for people with SMI.…”
Section: Resultsmentioning
confidence: 91%
“…Interventions to improve the physical health of schizophrenia patients, including modification of lifestyle choices such as smoking, diet, and exercise, have been effective 34). In clinical settings, it may be difficult to engage patients with severe mental illness in behavioral modification due to their low motivation and lack of acknowledgement of the need for physical health management 35). A motivation enhancement strategy is required to change patients’ unhealthy behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is worthwhile to stress that while awareness is definitely increasing, psychiatrists should be vigilant to the adverse metabolic effects of some second-generation antipsychotics ( 33 ), especially the risk of reward deficiency syndrome in substance user psychotic patients treated with full blocking D2 antagonist. To improve the current situation, additional efforts are still needed in order to improve training programs as shown in a recent survey of 35 countries ( 34 ).…”
Section: Discussionmentioning
confidence: 99%